Body size is more important than diet in determining stable-isotope estimates of trophic position in crocodilians - Villamarín, Francisco (2018)
The trophic position of a top predator, synonymous with food-chain length, is one of the most fundamental attributes of ecosystems. Stable isotope ratios of nitrogen (δ15N) have been used to estimate trophic position of organisms due to the predictable enrichment of 15N in consumer tissues relative to their diet. Previous studies in crocodilians have found upward ontogenetic shifts in their ‘trophic position’. However, such increases are not expected from what is known about crocodilian diets because ontogenetic shifts in diet relate to taxonomic categories of prey rather than shifts to prey from higher trophic levels. When we analysed dietary information from the literature on the four Amazonian crocodilians, ontogenetic shifts in dietary-based trophic position (TPdiet) were minimal, and differed from those estimated using δ15N data (TPSIA). Thus, ontogenetic shifts in TPSIA may result not only from dietary assimilation but also from trophic discrimination factors (TDF or Δ 15N) associated with body size. Using a unique TDF value to estimate trophic position of crocodilians of all sizes might obscure conclusions about ontogenetic shifts in trophic position. Our findings may change the way that researchers estimate trophic position of organisms that show orders of magnitude differences in size across their life span.